Desalted duck egg white nanogels as Pickering stabilizers for food-grade oil-in-water emulsion - Jingyun Zhao; Xiaohan Guo; Ze Chen; Yalei Dai; Hongshan Liang; Qianchun Deng; Shugang Li; Bin Zhou (Food Science and Human Wellness)
Achieving the reuse of traditional egg by-products, salted duck egg whites (SEW), is an urgent problem to be solved. In this current work, we constructed a heat-induced gel-assisted desalination method for SEW. Subsequently, a top-down way was utilized to prepare desalted duck egg protein nanogels (DEPN) with uniformly distributed diameters and their application in the oil/water (O/W) interface system was explored. The results revealed that the increase of DEPN concentration could lower the droplet size, however, the size was negatively correlated with the oil phase fraction. Moreover, the effect of pH, ionic strength, and temperature on the emulsion stability demonstrated that the DEPN-stabilized emulsion displayed superior physical stability under different conditions. The addition of NaCl resulted in the significant decrease in droplet size of the emulsion, while further increasing the NaCl concentration, the droplet size did not decrease accordingly. Besides, heat-treatment and cold-treatment had little negative effect on the stability of the emulsion. Even if the droplet size of the emulsion increased at 80 °C for 3 h, the morphology of the emulsion remained unchanged. Our study demonstrated DEPN had great potential as a stabilizer for food-grade Pickering emulsions.